Argumentation and explanation in the law - Rotolo, Antonino; Sartor, Giovanni (Frontiers in Artificial Intelligence, 2023)
This article investigates the conceptual connection between argumentation and explanation in the law and provides a formal account of it. The contribution is twofold. On the one hand, we offer a critical reconstruction of the concept of legal argument, justification and explanation of decision-making as it has been elaborated in legal theory and, above all, in AI & Law. On the other hand, we propose some definitions of explanation in the context of formal legal argumentation, showing a connection between formal justification and explanation.